PENINGKATAN MANAJEMEN KEUANGAN DI MTS ASY SYAAFIIYYAH KUWARASAN DENGAN METODE PROGRAM EVALUATION AND REVIEW TECHNIQUE SERTA CRITICAL PATH METHOD (PERT/CPM) MELALUI PELATIHAN DAN PENGUATAN KOORDINASI PENGELOLA MADRASAH - Wibawan, Agung; Wachidah, Siti Fauzatun; Hendrawan, Aji Kusumastuti (Jurnal Abdi Insani, 2024)
The financial management at MTs Asy Syaafiiyyah Kuwarasan that has been implemented so far is based on the type of expenditure and display of total costs at the end of the school year. This model of financial management has weaknesses in monitoring the achievement of work program indicators per time, and results in empty budgets in certain periods, which has an impact on other activities. Management's lack of understanding of financial governance causes overlapping financial reporting systems, which makes it difficult to review priority needs. The aim of carrying out this service is to provide a new understanding to madrasa administrators about the importance of managing financial reports using grouping activities per time using the Gantt Chart display in MS Project and monthly reports using MS Excel. The method used is a group discussion forum with the madrasah management and periodic review of the method for filling out the financial report template. The resulting template in Excel which is compiled based on RKAM (Madrasah Activity Plan and Budget) data produces a reporting display that is easier to analyze and provides an overview of the magnitude of the flow of money coming in and out of the madrasah. Through this template, it becomes easier for madrasah managers to display expenditure and income flows to external parties who need them. More transparent and accountable reporting by combining income information from BOS funds and committees is also one of the advantages of using this template. Through training activities and assistance in preparing financial report templates, madrasah managers gain a new understanding of management.